SOCIAL (media) CHANGE: enhancing national park tourism education and experiences with updated app technology - Hake, Bridget E. (Kansas State University, 2020)
Our national parks are at a crossroads right now balancing their two goals: risking deterioration by allowing all of “this and future generations” to use, or limiting access for all in order to “preserve unimpaired the natural and cultural resources and values of the National Park System” (National Park Service 2018). Shifts in communication, information, and travel have made national parks more accessible than ever which is causing some of our most treasured landscapes to become overcrowded and damaged (Pickering 2011). Media and campaigns have contributed heavily to park visitation since its conception, but new technology brings new ethical responsibility to advertising naturebased tourism. Social media and other apps have largely contributed to the misuse of our public lands with few positive applications (Tan and Lu 2019). This report explores the history of communications within the national parks, how new media is changing our interactions with parks, the negative impacts of continued mass tourism, and finally proposes a new public lands app that could potentially positively impact our parks and promote healthy tourism.
Keywords: National Parks; Social Media Landscape Architecture; Landscape Architecture